2018
DOI: 10.1111/epi.14029
|View full text |Cite|
|
Sign up to set email alerts
|

Electrocorticographic high‐gamma modulation with passive listening paradigm for pediatric extraoperative language mapping

Abstract: HGM associated with story listening is a specific determinant of left hemisphere ESM language sites. It can be used for presurgical language mapping in children who cannot cooperate with conventional language tasks requiring active engagement. Incorporation of additional language tasks, if feasible, can further improve the diagnostic accuracy of language localization with HGM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…You might answer “bird” or “plane,” if you are verbally asked: “What flies in the sky?” Word finding abilities in the visual or auditory domain are crucial for humans. Visual object naming (referred to as “picture naming” below) and auditory description naming (“auditory naming”) are commonly used for evaluation of baseline language competence as well as for localization of language‐related eloquent areas in patients scheduled to undergo epilepsy surgery . Transient language impairment elicited by electrical stimulation and task‐related neural activation on electrocorticography (ECoG) or functional MRI (fMRI) are useful biomarkers for localization of eloquent areas in clinical practice .…”
Section: Introductionmentioning
confidence: 99%
“…You might answer “bird” or “plane,” if you are verbally asked: “What flies in the sky?” Word finding abilities in the visual or auditory domain are crucial for humans. Visual object naming (referred to as “picture naming” below) and auditory description naming (“auditory naming”) are commonly used for evaluation of baseline language competence as well as for localization of language‐related eloquent areas in patients scheduled to undergo epilepsy surgery . Transient language impairment elicited by electrical stimulation and task‐related neural activation on electrocorticography (ECoG) or functional MRI (fMRI) are useful biomarkers for localization of eloquent areas in clinical practice .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, during story listening, age at onset of seizures also had a significant relationship with MI between Broca's area and Wernicke's area. 6,7,15,34,35 Despite efforts to ensure methodological rigor, this study has some unavoidable limitations. Linear regression models for mutual information (y-axis) between pairs of language cortical regions during picture naming are shown as functions of age (x-axis).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that HGM associated with hearing words (compared to hearing tones) involves Wernicke's area and PAC, sometimes also including cortical sites that do not show speech/language dysfunction on ESM. 7 Hence, increasing MI with age between Wernicke's area and FAC/PAC likely represents an important role of Wernicke's area in transferring information contained in auditory speech representations to association cortices. The thickness of the arrows corresponds with mean mutual information in the age group, whereas color indicates statistical significance (red, P ≤ 0.0032, Šidák-corrected P value for 16 independent regression models; orange, 0.05 ≤ P ≤ 0.0032, suggesting a trend but not meeting criteria for statistical significance; blue, P > 0.05) observations in children and showed that HGM during story listening has higher specificity and accuracy to determine ESM language sites in the posterior compared to frontal ROIs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations